2014
DOI: 10.1371/journal.pcbi.1003844
|View full text |Cite
|
Sign up to set email alerts
|

Multi-state Modeling of Biomolecules

Abstract: Multi-state modeling of biomolecules refers to a series of techniques used to represent and compute the behavior of biological molecules or complexes that can adopt a large number of possible functional states. Biological signaling systems often rely on complexes of biological macromolecules that can undergo several functionally significant modifications that are mutually compatible. Thus, they can exist in a very large number of functionally different states. Modeling such multi-state systems poses two proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 60 publications
0
41
0
Order By: Relevance
“…We also tested whether differences in the way biological entities are named affects recognition and grounding; we found that Wip1, WIP-1, WIP1, PPM1D, and Protein phosphatase 1D as well as ATM, Atm, Box 3: Rule-based modeling and PySB Accurate simulation of biochemical systems requires that every species be explicitly tracked through time. The combinatorial nature of protein complex assembly, post-translational modification, and related processes causes the number of possible molecular states in many signaling networks to explode and exceed the capacity for efficient simulation (Stefan et al, 2014). For example, full enumeration of complexes involved in EGF signaling would require more than 10 19 molecular species differing in their states of oligomerization, phosphorylation, and adapter protein binding ).…”
Section: Normalized Extraction Of Findings From Diverse Inputs Using mentioning
confidence: 99%
“…We also tested whether differences in the way biological entities are named affects recognition and grounding; we found that Wip1, WIP-1, WIP1, PPM1D, and Protein phosphatase 1D as well as ATM, Atm, Box 3: Rule-based modeling and PySB Accurate simulation of biochemical systems requires that every species be explicitly tracked through time. The combinatorial nature of protein complex assembly, post-translational modification, and related processes causes the number of possible molecular states in many signaling networks to explode and exceed the capacity for efficient simulation (Stefan et al, 2014). For example, full enumeration of complexes involved in EGF signaling would require more than 10 19 molecular species differing in their states of oligomerization, phosphorylation, and adapter protein binding ).…”
Section: Normalized Extraction Of Findings From Diverse Inputs Using mentioning
confidence: 99%
“…Although cell signaling has been studied for decades, we have limited knowledge about how modifications and binding at different sites of a protein are coupled (e.g., [20, 24, 88]). We argue that rules expressing a high degree of modularity represent a more natural starting point for model development than making assumptions for the sake of limiting network size.…”
Section: Uses and Advantages Of Rule-based Modelingmentioning
confidence: 99%
“…Here, we provide a brief introduction to rule-based modeling in systems biology, which is characterized by the use of local rules to represent biomolecular interactions [1824]. In biology, rule-based modeling has most often been used to study cell signaling systems, but this modeling paradigm is more broadly applicable [23, 2527].…”
Section: Introductionmentioning
confidence: 99%
“…Biomolecular interactions can be represented by formalized rules (Chylek et al, 2014a;Stefan et al, 2014). Collections of rules form rule-based models, which provide concise representations of biomolecular interaction networks and can be analyzed to obtain insights into how system-level behavior emerges from biomolecular interactions (Chylek et al, 2014a;Stefan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Collections of rules form rule-based models, which provide concise representations of biomolecular interaction networks and can be analyzed to obtain insights into how system-level behavior emerges from biomolecular interactions (Chylek et al, 2014a;Stefan et al, 2014). Rule-based models must be analyzed with specialized algorithms and software tools (Chylek et al, 2014a;Stefan et al, 2014), such as BioNetGen (Harris et al, 2015), which interprets models encoded in the BioNetGen language (BNGL) and provides deterministic, stochastic and hybrid forward simulation capabilities (Harris et al, 2015). To date, other critical methods of analysis, such as fitting (parameter estimation), have typically been applied ad hoc (e.g.…”
Section: Introductionmentioning
confidence: 99%